Morfologia, histologia e proteômica do testículo de codornas europeias alimentadas com anacardato de cálcio - Ferreira, Rafael de Sousa (2019)
The goal of this work was to assess the action of Calcium anacardate on morphological characteristics, histological and testicle proteomics and also epididymis of male breeding of quails. In this regard, 22 males aged 140 days were used and distributed in four treatments, t1 (6 animals), T2 (6 animals), T3 (5 animals) and T4 (5 animals) so that, with the exception of treatment 1 (control), in each treatment there was the addition of 0.25%; 0,50%; 0.75% calcium anacardate, respectively, during an experimental period of 210 days. In order to obtain morphometric data, the testicles were weighed and measured (length, diameter and volume). The gonadosomatic index was collected from the weight of the bird and the testicular weight. For the proteomic analysis of the testicles, techniques were used as protein extraction followed by separation of proteins by 1D SDS-PAGE method and used mass spectrometry to identify bands. About histology, the testicles and epididymis were placed in 50 ml tubes and fixed in a 10% formaldehyde solution. The samples underwent all histological processing and were then cut at 0.6 μm with the aid of a micrometer and stained for optical microcopy analysis. There was no significant difference in any of the morphometric data collected. Using the SDS-PAGE 1D electrophoresis technique, a total of 35 bands were identified where 13 bands were different from the others so that a difference in treatment was observed with 0.75% calcium anacardate control treatment (T1). A total of 152 proteins were identified where only 2% of total proteins have antioxidant function. The diameter of the seminiferous tubule and the amount of cells present in the seminiferous tubule were not influenced by the calcium anacardate level provided for quails, however, a significant difference was observed between the means in relation to the height of the seminiferous epithelium and diameter of the epididymal duct. From histological images, a difference was noted regarding histological structure and presence of cells in the treatments used. The testicular morphometry of quails is not altered by the value of up to 0.75% of anacardate and calcium. Protein expression in the testicle can be altered by the addition of 0.75% calcium anacardate, especially proteins related to oxidative stress. The addition from 0.50% calcium anacardate modifies the height of the germinal epithelium and the diameter of the epididymal duct, but does not result in effects on the diameter of the seminiferous tubule or the amount of germ cells.